Hepatocellular carcinoma cells express 25(OH)D-1α-hydroxylase and are able to convert 25(OH)D to 1α, 25(OH)2D, leading to the 25(OH)D-induced growth inhibition. Issue 154 (November 2015) - Chiang, Kun-Chun; Yen, Cho-Li; Yeh, Chun-Nan; Hsu, Jun-Te; Chen, Li-Wei; Kuo, Sheng-Fong; Wang, Shang-Yu; Sun, Chi-Chin; Kittaka, Atsushi; Chen, Tai C.; Yeh, Ta-Sen; Hsu, Shu-Yuan; et al.
Highlights: In this study, we found CYP27B1 expression in human hepatocyte and HCC. HepG2 cells were able to convert 25(OH)D to 1α, 25(OH)2D, leading to the growth inhibition by 25(OH)D. Our data showed the application of 25(OH)D and CYP27B1 gene transfection therapy could effectively inhibit HepG2 cell growth. Abstract: Hepatocellular carcinoma (HCC) is the most diagnosed liver cancer without effective treatments available for advanced HCC. Vitamin D is getting popular due to its anti-cancer characteristics. However, the clinical application of 1α, 25(OH)2 D, the active form of vitamin, is hampered by its hypercalcemia side effect. 1α, 25(OH)2 D is converted from 25(OH)D, the index of serum vitamin D status, by CYP27B1, which is originally found in kidneys but recently detected in non-renal tissues. 25(OH)D has been shown to repress some cancers expressing CYP27B1 due to the local conversion of 25(OH)D to 1α, 25(OH)2 D, which works in a intra-, auto-, or paracrine manner and thus minimizes the risk of hypercalcemia. In this study, we found CYP27B1 expression in human hepatocyte, HCC, and HepG2 cells. As we treated HepG2 cells with 25(OH)D, the 1α, 25(OH)2 D target gene CYP24A1 expression was increased and was further upregulated as CYP27B1 transfection or downregulated as CYP27B1 knockdown. Other 1α, 25(OH)2 D target genes in HepG2 cells, p21 and p27 were also stimulated by 25(OH)D after CYP27B1 transfection. Further, 25(OH)D could inhibit HepG2 cells growth, which was potentiated by CYP27B1 transfection. Collectively, we showed for the first time that HCC expressed CYP27B1 and was able to covert 25(OH)D to 1α, 25(OH)2 D in vitro, thus responsive to 25(OH)D treatment. Our data justifies the application of 25(OH)D and CYP27B1 gene transfection therapy in further HCC treatment studies.